2006
DOI: 10.1016/j.str.2006.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and Conformational Entropy in Protein-Protein Binding

Abstract: To better understand the interplay between protein-protein binding and protein dynamics, we analyzed molecular dynamics simulations of 17 protein-protein complexes and their unbound components. Complex formation does not restrict the conformational freedom of the partner proteins as a whole, but, rather, it leads to a redistribution of dynamics. We calculate the change in conformational entropy for seven complexes with quasiharmonic analysis. We see significant loss, but also increased or unchanged conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(81 citation statements)
references
References 77 publications
(114 reference statements)
2
78
0
1
Order By: Relevance
“…It is interesting that additional connectivity in these regions softens the twist mode, so as to lower the energy of motion along it. If an analogous effect occurred in actually binding a ligand, it would be in accord with the increase in entropy calculated for other systems (23).…”
Section: Resultssupporting
confidence: 72%
“…It is interesting that additional connectivity in these regions softens the twist mode, so as to lower the energy of motion along it. If an analogous effect occurred in actually binding a ligand, it would be in accord with the increase in entropy calculated for other systems (23).…”
Section: Resultssupporting
confidence: 72%
“…However, the flexibility of the linker as well as the cooperative stabilization of the UIM helix can overcome the entropic penalty. One has to keep in mind that flexibility has an important influence on the thermodynamics of binding and may both favor and disfavor association (56). In the light of our results, the differences between the binding of VHS-UIM to mono-Ub, Lys 48 (54) demonstrated that the linker length and composition modulated the affinity of RAP80-tUIM for Lys 63 -Ub 2 in a periodic fashion.…”
Section: Discussionmentioning
confidence: 64%
“…In protein-protein interactions, the enthalpy driving force is related to the change in the entire noncovalent energy upon binding, whereas entropy is affected by conformational changes and water displacement from the interface (85,86). Previous studies have shown that one-third of all interface residues are observed to undergo conformational changes (87,88).…”
Section: Discussionmentioning
confidence: 99%